2018
DOI: 10.1093/ndt/gfy224
|View full text |Cite|
|
Sign up to set email alerts
|

Current approaches to middle molecule removal: room for innovation

Abstract: Aggressive removal of middle molecules or larger low-molecular-weight proteins (LMWPs) has been a growing concern following studies on their harmful effects on the mortality and morbidity of chronic dialysis patients. To remove larger LMWPs and some protein-bound uremic toxins (PBUTs), high- and medium-cutoff (HCOs and MCOs, respectively) membranes, convective therapy and protein adsorptive membranes are available. When we use HCO or MCO membranes for convective therapy, we have to take care to avoid massive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 76 publications
1
56
0
7
Order By: Relevance
“…In general, dialysers are assigned into one of four categories according to the degree of removal of molecules such as beta‐2 microglobulin and albumin: Ia, Ib, IIa and IIb . In this study, the dialysers were divided into two categories, Ia plus IIa and Ib plus IIb, according to removal of large molecules such as albumin.…”
Section: Methodsmentioning
confidence: 99%
“…In general, dialysers are assigned into one of four categories according to the degree of removal of molecules such as beta‐2 microglobulin and albumin: Ia, Ib, IIa and IIb . In this study, the dialysers were divided into two categories, Ia plus IIa and Ib plus IIb, according to removal of large molecules such as albumin.…”
Section: Methodsmentioning
confidence: 99%
“…The predilution method can freely increase the substitution volume even with a low blood flow rate and is able to improve the solute removal efficiency of low molecular weight proteins (LMWPs). Furthermore, if we use a large pore size filter in the predilution method, we can remove larger LMWPs without explosive albumin leakage [5]. The Japanese pioneer doctors found that dialysis prescriptions with larger LMWP removal incurring a certain level of albumin loss have improved various uremic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese pioneer doctors found that dialysis prescriptions with larger LMWP removal incurring a certain level of albumin loss have improved various uremic symptoms. Based on these experiences, "protein permeable dialysis" has developed in Japan [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk of depletion of important nutrients during dialysis sessions with highly permeable membranes cannot be ruled out, and, while the advantages of better depuration are clear in young, well-nourished patients, it is still far from certain that high flow hemodiafiltration produces advantages for malnourished patients [26][27][28][29][30][31][32][33].…”
Section: Lipidsmentioning
confidence: 99%
“…Moreover, dialysis prescription varies widely, and very different treatments may be gathered under the same name; information on the dialysis schedule is often incomplete, thus making comparisons and implementing strategies can be challenging [29][30][31].…”
Section: Mia: Malnutrition Inflammation Atherosclerosis Syndromementioning
confidence: 99%